2021
DOI: 10.1111/ecc.13520
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient palliative care utilisation among patients with gallbladder cancer in the United States: A 10‐year perspective

Abstract: Objectives: Gallbladder cancer (GBC) is a rare, poor-prognosis cancer with unique demographics, comorbidities and a paucity of research. This study investigated inpatient palliative care and its associations with demographics, comorbidities (e.g., obesity), length of stay and hospital charges in GBC in US hospitals (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016).Methods: Data were extracted from the National Inpatient Sample (NIS) database that contains deidentified clinical and nonclinical inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Another explanation for our findings could be that male and racial/ethnic minority groups might underutilize hospice and palliative care services, a type of care that lower hospital LOS, charges, and mortality. Previous studies have indicated that male and racial/ethnic minority groups are less proactive about choosing a hospital palliative care referral or enrolling in hospice when their medical care is futile, potentially leading to longer hospital LOS and higher hospital charges and mortality rates (23,29,30). This mechanism is also applied to the Medicaid recipients (29).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for our findings could be that male and racial/ethnic minority groups might underutilize hospice and palliative care services, a type of care that lower hospital LOS, charges, and mortality. Previous studies have indicated that male and racial/ethnic minority groups are less proactive about choosing a hospital palliative care referral or enrolling in hospice when their medical care is futile, potentially leading to longer hospital LOS and higher hospital charges and mortality rates (23,29,30). This mechanism is also applied to the Medicaid recipients (29).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 29 , 30 Moreover, offering palliative care at home would particularly expand such care to minorities whose attitudes are usually against placing their loved ones in institutions. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…14 Home palliative care combined with telehealth can particularly expand palliative care services to rural areas where there has always been a significant shortage of palliative care professionals. 9,29,30 Moreover, offering palliative care at home would particularly expand such care to minorities whose attitudes are usually against placing their loved ones in institutions. 30,31 Policy Implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mojtahedi et al showed that only 10% of all hospitalised patients with gallbladder cancer (a rare poor‐prognosis cancer) in the United States is referred to palliative care. Fortunately, the use of palliative care in this group has slightly increased over the past 10 years (Mojtahedi et al, 2021). Also in Sweden, as shown by Adolfsson et al, physicians from various hospital departments stated that they still introduce palliative care rather late in the cancer trajectory, despite positive attitudes towards the benefits of integration of palliative care into oncology (Adolfsson et al, 2022).…”
mentioning
confidence: 99%